An experiential approach to developing radiological content for public health nursing: Lessons from a nuclear disaster. Issue 2 (3rd January 2020) - Kawasaki, Chie; Kitamiya, Chiaki; Yoshida, Koji; Omori, Junko; Porter, Sarah; Asahara, Kiyomi
Abstract: Objective: This study identified the radiological content required for PHNs and public health nursing students based on PHNs' experiences caring for people affected by the 2011 Fukushima Daiichi nuclear power plant accident. Design: We used qualitative research, interviews, and content analysis. Sample: Participants were eight PHNs employed by local governments in Fukushima and neighboring prefectures. Results: Six content themes regarding the nuclear disaster were identified: (a) basic knowledge about radiation, (b) public health nursing activities in emergency exposure situations, (c) management in emergency exposure situations, (d) consultation to support residents affected by the nuclear disaster, (e) activities in the existing exposure situations, and (f) disaster preparedness in the planned exposure situations. Necessary content shifted depending on the phase of the nuclear disaster recovery. Conclusions: The use of the experiences of PHNs after the nuclear power plant accident to inform PHNs and public health nursing students will enable PHNs to respond appropriately and support people without difficulties. Comprehensive radiation content is needed to address the range of situations caused by nuclear disaster.